Supply Chain Performance Analysis of Construction Materials in the Core Government Center (KIPP) Development Project in Nabire Using the SCOR Method - Agung Nugroho (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aims to analyze the performance of the construction material supply chain in the Government Core Area (KIPP) development project in Nabire, Central Papua, using the Supply Chain Operations Reference (SCOR) method. The novelty of this research lies in its empirical application of SCOR to a government infrastructure project in a geographically remote region, addressing an underexplored research gap in the existing literature. A mixed-methods design was employed, with structured questionnaires (5-point Likert scale) administered to 32 purposively selected respondents representing key supply chain stakeholders. The instrument was validated using Pearson correlation and tested for reliability using Cronbach's Alpha. Performance was measured across five SCOR processes: plan, source, make, deliver, and return. Validity testing confirmed all 31 items were valid (r calculated > r table = 0.349), and all processes were reliable (α = 0.767–0.813). Performance measurement results indicate that all five SCOR processes fall within the Moderate category: Plan (Mean=3.34; SD=0.888), Source (Mean=3.38; SD=0.886), Make (Mean=3.40; SD=0.893), Deliver (Mean=3.45; SD=0.831), and Return (Mean=3.34; SD=0.937). Key constraints include dependence on external suppliers, suboptimal port and road infrastructure, and coordination gaps among stakeholders. Recommended improvement strategies include supplier diversification, adoption of supply chain information systems, logistics optimization, and development of local material sources. Keywords: Supply Chain Performance, Construction, SCOR